(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Karnasrava (discharge through the ear) is one of the most common diseases in the ear. Ayurveda describes twenty-eight types of Karna rogas and Karnasrava is a major ailment among these diseases. It has a great impact on the socio-economic lifestyle of people with larger complications. So, it needs more attention towards treatment. In modern science, karnasrava can be correlated with Chronic Suppurative Otitis Media. The treatment strategies are very limited as they are not free from side effects and risks.2,3 Ayurveda specifies a multimodal tactic for this problem with the use of herbal medications. Triphala guggul is one of the choices as a drug.4 In this article, Karnasrav and the role of Triphala guggul in management have been discussed.